Development of permeable reactive barrier for phosphorus removal - Oliveira, M. (2010)
Permeable reactive barriers were developed for phosphorus removal. The barrier consists in an organic-inorganic hybrid material, which allows water and others species to flow through it, while selectively removes the contaminants. Polyethylene oxide (POE) and aluminium oxide (Al2O3) were used as the organic and the inorganic parts, respectively. The hybrid material was obtained by sol-gel reaction, using aluminium isopropoxide as inorganic percursor in order to attain Al2O3. The hybrid material produced was characterized by FT-IR spectroscopy and thermogravimetry. The previous tests for phosphorus removal have shown the effectiveness capacity of the developed material to remove it.